Sistem Pendukung Keputusan Prediksi Harga Rumah Kost untuk Mahasiswa IT Telkom Purwokerto Menggunakan Metode Fuzzy Tsukamoto Berbasis Web - Ummi Athiyah; Arnelka Hananta; Taufik Maulidi; Vico Meylana Eka Putra; Theo Felix Harianto Purba; Elisabeth Angeline Wilhelmina Bakowatun (Research Group of Data Engineering, Faculty of Informatics, 2021)
Purwokerto City is a developing city located in the southwestern part of Central Java Province. Purwokerto is known as thecity of students in Central Java. It is not wrong if many newcomers choose to continue their studies at the favoriteuniversities in this city. One of the universities in this city is the Telkom Purwokerto Institute of Technology. With so manynewcomers who want to continue their studies in this city. Of course, you need a place to live like a boarding house. Eachboarding house has different facilities and also has varying prices, making it difficult for newcomers to choose the boardinghouse. So a decision support system is needed to help students of the Telkom Purwokerto Institute of Technology to make theright decision in predicting the price of a boarding house when choosing a boarding house according to the existing criteriaand funds using the Fuzzy Tsukamoto method.